2019
DOI: 10.1038/s41467-019-09709-6
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic fibroblast contractions attract remote macrophages in fibrillar collagen matrix

Abstract: Macrophage (Mϕ)-fibroblast interactions coordinate tissue repair after injury whereas miscommunications can result in pathological healing and fibrosis. We show that contracting fibroblasts generate deformation fields in fibrillar collagen matrix that provide far-reaching physical cues for Mϕ. Within collagen deformation fields created by fibroblasts or actuated microneedles, Mϕ migrate towards the force source from several hundreds of micrometers away. The presence of a dynamic force source in the matrix is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(188 citation statements)
references
References 65 publications
6
182
0
Order By: Relevance
“…We use the model to study fibroblasts cultured on fibronectin-coated micropatterned substrates. In our study, we focus on the stationary behavior of cells where cells have adopted the shape of the substrate while the model can be readily extended to study time-dependent behavior of cells as shown in our recent publications (37). All our experiments are also carried out in the stationary configuration where fibroblasts are fully constrained to the micropatterned substrate before and after drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…We use the model to study fibroblasts cultured on fibronectin-coated micropatterned substrates. In our study, we focus on the stationary behavior of cells where cells have adopted the shape of the substrate while the model can be readily extended to study time-dependent behavior of cells as shown in our recent publications (37). All our experiments are also carried out in the stationary configuration where fibroblasts are fully constrained to the micropatterned substrate before and after drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Monocultured macrophages exhibited minimal migration from the seeding plane, whereas co-cultured macrophages migrated further into the ECM toward the tumor layer especially at 24 and 48 hours ( Fig 5B&C). Therefore, the maximum migration distance for the monoculture condition was used to threshold passive from active macrophage migration at each time point (Fig 5B-D) 75 . Actively-migrating macrophages in co-culture have lower redox ratio at all time points, suggesting that these macrophages shift towards oxidative metabolism to enhance migration in the tumor microenvironment ( Fig 5E).…”
Section: Figure 4: Metabolic Autofluorescence Imaging Of Mouse Macropmentioning
confidence: 99%
“…Macrophages contribute with cytokines and growth factors necessary for wound healing (Klinkert et al, 2017). In addition, macrophage–fibroblast interactions are important during myofibroblast differentiation (Pakshir et al, 2019). Since diabetes may alter macrophage phenotype in diabetic wounds (Iacopino, 1995; Mirza et al, 2015), it is possible that dysfunctional macrophages may be associated with alterations in myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%